2006
DOI: 10.1111/j.1365-3156.2005.01546.x
|View full text |Cite
|
Sign up to set email alerts
|

Financial implications of skilled attendance at delivery in Nepal

Abstract: Summaryobjective To measure costs and willingness-to-pay for delivery care services in 8 districts of Nepal. method Household costs were used to estimate total resource requirements to finance: (1) the current pattern of service use; (2) all women to deliver in a health facility; (3) skilled attendance at home deliveries with timely referral of complicated cases to a facility offering comprehensive obstetric services.results The average cost to a household of a home delivery ranged from 410 RS ($5.43) (with a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
105
4
1

Year Published

2007
2007
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 97 publications
(122 citation statements)
references
References 19 publications
9
105
4
1
Order By: Relevance
“…Nepal, for example, is piloting a policy that combines subsidies for all deliveries with free deliveries and assistance with costs such as transport for women in poorer regions. 21,22 There is experience in Yunnan, China, and Bangladesh in using vouchers that entitle poor women to free delivery services. 23 In Bolivia, a social insurance scheme, which provides free care for pregnant women and under-fives, has increased utilisation, especially by the poor.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nepal, for example, is piloting a policy that combines subsidies for all deliveries with free deliveries and assistance with costs such as transport for women in poorer regions. 21,22 There is experience in Yunnan, China, and Bangladesh in using vouchers that entitle poor women to free delivery services. 23 In Bolivia, a social insurance scheme, which provides free care for pregnant women and under-fives, has increased utilisation, especially by the poor.…”
Section: Discussionmentioning
confidence: 99%
“…Given the relatively high cost-recovery rates in Ghana and reasonable geographic access to services, the emphasis on reducing fees was appropriate, whereas in Nepal, transport costs constitute the largest cost element for households in accessing maternal care. 22 Ghana's experience suggests that where facilities are understaffed, as in much of subSaharan Africa, they should be closely involved in the development of policies such as these and a package of incentives provided for staff to deliver quality care. The health worker survey in this evaluation found that although very few direct financial incentives were provided as part of the delivery exemption policy, the overall increase in pay as part of wider pay reforms in the public sector compensated for increased hours of work for different types of staff.…”
Section: Discussionmentioning
confidence: 99%
“…1,24,26 Of these obstacles, the cost of services and other financial barriers are perceived by poor women as one of the major reasons against delivering in a health facility. 2,3,27 Health policy and decision-makers have therefore focused attention on mechanisms to address the cost barriers that women face.…”
Section: Difficulties In Access To Maternal Health Carementioning
confidence: 99%
“…3,12 Skilled providers are also incentivised for facility deliveries and for home deliveries, given that difficult terrain in Nepal renders many facilities inaccessible. 27,36 Health providers pay women in cash directly upon discharge. Rather than target the scheme towards the poorest, the government chose universal targeting, ostensibly for equity though it is also easier to manage and popular politically.…”
Section: Nepalmentioning
confidence: 99%
“…Also, knowledge of maternity-related expense and its determinants is useful for health authorities to focus public resources and target financial assistance or exemption guidelines towards the 'most needy' (7). Expenses for maternal and neonatal care in antepartum, intrapartum and postpartum services has been well-documented in several studies (7-13) conducted in developed countries and in South Asian countries (14)(15)(16)(17), allowing for more efficient use of resources. However, there is a paucity of such data from India.…”
Section: Introductionmentioning
confidence: 99%